Adolescent Substance Abuse Risk: A Comparison of Pediatric Emergency Care Applied Research Network Emergency Department Patients and 2 Nationally Representative Samples. Issue 9 (September 2021) - Chun, Thomas H.; Chernick, Lauren S.; Ahmad, Fahd A.; Ranney, Megan L.; Shenoi, Rohit P.; Casper, T. Charles; Fein, Joel A.; Grupp-Phelan, Jackie; McAninch, B.; Powell, Elizabeth C.; Bromberg, Julie R.; Linakis, James G.; et al.
Abstract : Objectives: The aim of this study was to understand the prevalence of alcohol and other substance use among teenagers in generalized samples. Methods: This study compared the alcohol and other substance use of adolescents enrolled in a screening study across 16 Pediatric Emergency Care Applied Research Network emergency departments (EDs) (ASSESS) with those sampled in 2 nationally representative surveys, the Youth Risk Behavior Surveillance System (YRBSS) and the National Survey of Drug Use and Health (NSDUH). The analysis includes 3362 ASSESS participants and 11, 142 YRBSS and 12, 086 NSDUH respondents. Results: The ASSESS patients had a similar profile to the NSDUH sample, with small differences in marijuana and cocaine use and age at first tobacco smoking and smoking within the last 30 days and higher use of snuff or chewing tobacco. The YRBSS participants had higher rates of using marijuana, snuff/chewing tobacco, methamphetamine, and hallucinogens and higher smoking rates compared with ASSESS and NSDUH. Conclusions: Adolescents visiting Pediatric Emergency Care Applied Research Network EDs have substantial rates of substance use, similar to other nationally representative studies on this topic, although not as high as a school-based survey. Future ED studies should continue to investigate adolescent substance use, including exploring optimal methods of survey administration.